Good Corporate Governance and Company's Financial Performance with a Perspective Agency Theory in Companies Listed in The LQ45 Index - Eka Oktafia; Siti Ridloah; Mochamad Akbar (Management Analysis Journal, 2025)
This study examines the impact of good corporate governance on the company's financial performance. The population in this study are companies listed in the LQ45 Index for the 2017-2021 period. This study used a purposive sampling technique and obtained 28 companies, with as many as 140 observations. The result shows that managerial ownership has no significant effect on the company’s financial performance. The variable size of the board of directors has a significant positive effect on the company's financial performance. The independent commissioner variable has no significant effect on the company's financial performance. Audit committee meeting variables and gender diversity have no significant effect on the company's financial performance. Firm size as a control variable has no significant effect on company finances, and leverage as a control variable has a significant negative effect on the company's financial performance. Further researchers are also advised to examine other factors related to good corporate governance